Penyerapan Ion Logam Merkuri Menggunakan Arang Aktif Limbah Kulit Pisang Kepok (Musa paradisiaca Formatypica): The Adsorption of Mercury Metal Ion Using Kepok Banana’s Peel Waste (Musa paradisiaca Formatypica) Charcoal - Musafira; Dzulkifli; Fadrinah; Laila Qadrini (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
This research aimed to determine the percentage of mercury metal ion adsorbed in kapok banana peel’s activated carbon. It was done by applying Completely Randomized Design (CRD) with 6 variations of contact time, pH, and mercury concentration (i.e 10, 20, 30, 40, 50, 60 minutes; pH of 1, 2, 3, 4, 5, 6; and concentration of 10, 20, 30, 40, 50, 60 ppm, accordingly). The result showed that the equilibrium time was reached at 30 minutes, the maximum pH was reached at pH 5 and the maximum of adsorbed mercury ion at 40 ppm of mercury ion concentration. The adsorption percentages of those parameters were 61%, 98%, and 99%, respectively. Keywords: Kepok banana’s peel, charcoal, mercury metal ion.